2018
DOI: 10.1111/bjd.17190
|View full text |Cite
|
Sign up to set email alerts
|

Reference method for digital surface measurement of target lesions in vitiligo: a comparative analysis

Abstract: This study confirmed the reliability, validity and feasibility of two functions in ImageJ to measure target lesions in vitiligo. Based on the feasibility and included three-dimensional aspects, transparent sheets measured with the ImageJ 'wand' function can be proposed for future trials as a reference method to investigate the criterion validity of other digital instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…A recent publication introduced a delicate method to generate VASI automatically, through superpixel‐generated computerized digital image analysis of clinical photographs with ImageJ 246 . Another study proposed a protocol for calculating the true depigmentation area which could serve as a “gold standard” for validation of other digital tools 247 . The combination of these two methods might facilitate both vitiligo diagnosis and therapeutic efficacy assessment.…”
Section: Adaptive Immune Activationmentioning
confidence: 99%
“…A recent publication introduced a delicate method to generate VASI automatically, through superpixel‐generated computerized digital image analysis of clinical photographs with ImageJ 246 . Another study proposed a protocol for calculating the true depigmentation area which could serve as a “gold standard” for validation of other digital tools 247 . The combination of these two methods might facilitate both vitiligo diagnosis and therapeutic efficacy assessment.…”
Section: Adaptive Immune Activationmentioning
confidence: 99%
“…The primary outcome of our study was percent repigmentation assessed by planimetry, which has been validated for use in vitiligo and alopecia areata. 20 This method despite being accurate and reproducible, is technically demanding and time consuming, reducing its practicality for clinical practice and research, which might explain the scarce reports on this outcome to date. 21 Scarcity in planimetry reports for assessing repigmentation necessitated the adoption of multiple other endpoints pertaining to speed of response, percentage of patients showing moderate to excellent (50–100%) repigmentation, cosmetic matching, patient satisfaction, and technique tolerability, taking into consideration both physician and patients’ perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Four methods for UV exposure in vitiligo photography are as follows: (i) hand‐held Wood’s lamps (Wood’s lamps), these are the most commonly known in the field of dermatology and vitiligo, (ii) soft boxes with UV lamps without the translucent cloths (soft boxes), by reflecting the light towards the patient these can potentially reduce shadow forming, (iii) UV flash attached to the camera (camera flash), this device is potentially easy to use, and (iv) separate high output UV flash (high output flash), described in a previous study by van Geel et al All four methods are shown in Fig. .…”
Section: Introductionmentioning
confidence: 99%
“…These scoring systems could benefit from large area photography. The UV set‐up may influence the outcomes of research urging efforts for optimization and standardization . The objective of our study was to compare UV light set‐ups for vitiligo photography regarding image quality and ease of use.…”
Section: Introductionmentioning
confidence: 99%